The Effect of Promotion and Quality of Service on Consumer Purchase Decisions of Carpet Products in PT. Belindo International Carpet in Cikupa Tangerang - Jasmani Jasmani; Umi Narimawati; Azhar Affandi; Sidik Priadana; Heri Erlangga (Peneliti.net, 2022)
This study aims to determine the effect of promotion and service quality on purchasing decisions at PT. Belindo International Carpet in Cikupa Tangerang. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that promotion has a significant effect on purchasing decisions by 44.8%, hypothesis testing is obtained t count > t table or (8,914 > 1,984). Service quality has a significant effect on purchasing decisions by 36.9%, hypothesis testing is obtained t count > t table or (7.571 > 1.984). Promotion and service quality simultaneously have a significant effect on purchasing decisions with the regression equation Y = 10.849 + 0.422X1 + 0.316X2 and the contribution of the influence is 52.5%, hypothesis testing is obtained F count > F table or (53.644 > 2,700).